Dietary lecithin decreases skeletal muscle COL1A1 and COL3A1 gene expression in finisher gilts - Akit, Henny; Collins, Cherie; Fahri, Fahri T.; Hung, Alex; D'Souza , Darryl Nicholas; Leury, Brian J.; Dunshea, Frank Rowland (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
The purpose of this study was to investigate the effect of dietary lecithin on skeletal muscle gene expression of collagen precursors and enzymes involved in collagen synthesis and degradation. Finisher gilts with an average start weight of 55.9 ± 2.22 kg were fed diets containing either 0, 4, 20 or 80 g/kg soybean lecithin prior to harvest for six weeks and the rectus abdominis muscle gene expression profile was analyzed by quantitative real-time PCR. Lecithin treatment down-regulated Type I (α1) procollagen (COL1A1) and Type III (α1) procollagen (COL3A1) mRNA expression (p < 0.05, respectively), indicating a decrease in the precursors for collagen synthesis. The α-subunit of prolyl 4-hydroxylase (P4H) mRNA expression also tended to be down-regulated (p = 0.056), indicating a decrease in collagen synthesis. Decreased matrix metalloproteinase-1 (MMP-1) mRNA expression may reflect a positive regulatory response to the reduced collagen synthesis in muscle from the pigs fed lecithin (p = 0.035). Lecithin had no effect on tissue inhibitor metalloproteinase-1 (TIMP-1), matrix metalloproteinase-13 (MMP-13) and lysyl oxidase mRNA expression. In conclusion, lecithin down-regulated COL1A1 and COL3A1 as well as tended to down-regulate α-subunit P4H expression. However, determination of muscle collagen content and solubility are required to support the gene functions.